Conjunctival ultraviolet autofluorescence area, but not intensity, is associated with myopia. (16th August 2018) - Kearney, Stephanie; O'Donoghue, Lisa; Pourshahidi, Laura K; Richardson, Patrick; Laird, Eamon; Healy, Martin; Saunders, Kathryn J
Abstract : Background: Conjunctival ultraviolet autofluorescence (CUVAF) has been used as a biomarker of time spent outdoors. Smaller CUVAF area is associated with myopia in southern hemisphere cohorts. Further research is required to determine if this association is replicated in northern latitudes and whether average CUVAF intensity is a valuable metric. This prospective study explored the association between myopia, CUVAF (area and intensity) and additional indicators of sun exposure (vitamin D3 and self‐reported sun exposure preferences) across seasons at a location of 55° north. Methods: Young adults (age 18–20) provided blood samples biannually (March/April and September/October) over an 18‐month period (four phases) for the assessment of 25‐hydroxyvitamin D (25(OH)D3 ) concentrations (liquid chromatography‐tandem mass spectrometry). CUVAF (total area, average intensity) and self‐reported sun exposure preferences were recorded at each phase. Axial length and corneal radius were measured. Refractive error was measured by autorefractor and spherical equivalent refraction used to classify participants into refractive groups: myopic (spherical equivalent refraction ≤ −0.50 DS) or non‐myopic. Results: Fifty‐four participants (24 myopes, 30 non‐myopes) participated. CUVAF area was negatively associated with the presence of myopia (odds ratio = 0.94, 95 per cent confidence interval = 0.90–0.98, p = 0.002). Myopes = 4.5 mm 2 (interquartile range [IQR] 0.95–6.4 mm 2 ), non‐myopes = 7.0 mm 2 (IQR = 2.0–10.7 mm 2 ). No significant association was found between CUVAF intensity and refractive group (p = 0.17). There was no significant association between sun exposure preferences or serum concentration of 25(OH)D3 and refractive status (all p ≥ 0.21). CUVAF measures were not associated with ocular biometry measures (all p ≥ 0.084). CUVAF area was unaffected by season (all p ≥ 0.45) and variations in CUVAF area over the study period did not exceed the repeatability of the measurement technique. Conclusion: Myopia was associated with smaller areas of CUVAF indicative of less cumulative ultraviolet‐B exposure. These findings suggest that CUVAF measures are a useful, non‐invasive biomarker of the time spent outdoors in adults in northern hemisphere populations.